In Vivo Test of Rhizophora mucronata Mangrove Extract From Pangandaran Coast Towards Nile Tilapia Oreochromis niloticus infected by Vibrio harveyi - Yeni Mulyani; Kiki Haetami; Lesta Krismawati Baeha; Sulastri Arsad; Fiddy Semba Prasetiya (Journal of Aquaculture and Fish Health, 2020)
This study aims to determine the effectiveness of Rhizophora Mucronata’s bark extract in curing Vibrio harveyi infection in nile tilapia fish by challenge testing (in vivo test). It was conducted in October 2018-May 2019 at the Central Laboratory of Universitas Padjadjaran and Building-4 of Aquaculture and Hatchery Laboratory in the Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran. This research used microdilution method to determine the Minimum Inhibitory Concentration (MIC) value of R.mucronata’s bark extracts and laboratory experimental method with a Completely Randomized Design (CRD) model for challenge testing (in vivo) which consisted of 5 treatments and 3 replicates where the given treatment varied in concentrations. These various concentrations that were given started from A (0 ppm / control), B (16 ppm), C (32 ppm), D (48 ppm), and E (64 ppm). The observed parameters were inhibitory antibacterial activity for MIC and survival rate, as well as clinical symptoms and water quality for the challenge test. Survival Rate data of nile tilapia seedlings was analyzed by regression analysis. The observation results of MIC, MBC values, clinical symptoms and water quality were analyzed descriptively. The results showed the Minimum Inhibitory Concentration value of R.mucronata bark extract at a concentration of 6,250 ppm while its Minimum Bacteriocidal Concentration value at 50,000 ppm. The fish tolerance test results towards the extract (LC50 test) is 64 ppm. Differences in treatment produced results that have significant effects on survival rate. The use of Rhizophora Mucronata bark extract at a dose of 64 ppm resulted in the highest survival rate of Nile tilapia fish as high as 76.66%.